Ultrasound-assisted extraction of bioactive compounds from plant sources: optimization, kinetic, and modeling study - Teixeira, Bárbara Avancini (2023)
In recent years, emerging technologies, such as ultrasound, have been implemented in the area of bioactive compound extraction because they present a series of advantages when compared to conventional technologies. Such advantages can range from a decrease in process time, energy consumption, and use of solvents, as well as an increase in the recovery of target compounds, efficiency, and productivity of the process. In this context, the objective of this study was to optimize the ultrasound- assisted extraction of bioactive compounds (anthocyanins and total phenolics) from three raw materials from plant sources: raspberries (raw material rich in simple carbohydrates such as sucrose and fructose), purple tomato ( vegetable that contains fibers and other bioactive compounds like lycopene), and purple sweet potato (vegetable rich in carbohydrates like starch). For the optimization of the extraction process of bioactive compounds using ultrasound, three process variables were studied: time (min), temperature (°C) and solid:liquid ratio (m/v), using the Box- Behnken Design. From the data generated by the experimental design, it was possible to generate second-order regression equations, Pareto charts, and desirability profiles. The desirability profile was the tool that enabled the optimization of the processes, through the simultaneous combination of the studied variables, in order to achieve the highest recovery of the bioactive target compounds. The data predicted by the desirability profile were experimentally validated in the laboratory with satisfactory precision, for the three raw materials under study. In sequence, the optimized ultrasound-assisted extraction process was compared to the conventional extraction process, by maceration extraction with solvents. In all cases, the use of ultrasound significantly increased the recovery of the bioactive target compounds. The kinetic and modeling studies were only developed for raspberry and purple sweet potato. For raspberry, only a mathematical model was validated. While for the purple sweet potato, three mathematical models were validated. Furthermore, the three raw materials studied were analyzed under the lens of scanning electron microscopy, in order to observe the structural changes attributed to the action of ultrasound on the raw materials. In summary, the studies indicated that the ultrasound-assisted extraction process is an efficient technology for extracting bioactive compounds from plant sources. Keywords: Ultrasound. Extraction. Bioactive compounds. Optimization. Kinetics. Modeling.